Prevention of Incisional Hernias after Open Abdomen Treatment - Berrevoet, Frederik (Frontiers in Surgery, 2018)
Management of the open abdomen patient is difficult and primary closure of the fascial edges is essential to obtain best patients’ outcome regardless of the initial etiology of the open abdomen. The use of temporary abdominal closure devices is nowadays the gold standard to have the highest closure rates with mesh mediated fascial traction as the proposed standard of care. However, the incidence of incisional hernias, although much more controlled than when leaving an abdomen open, is high and reaches up to 65%. As shown for other high risk patient subgroups, such as obese patients, patients after abdominal aneurysm treatment and patients with former –ostomy sites, prevention of incisional hernias might be key to further optimize patient measured outcomes after open abdomen treatment. In this overview, current available modalities to possible decrease the incidence of incisional hernia are discussed. Most of these preventive options have been shown effective in giant ventral hernia repair and might work effectively in this patient cohort as well.